The Verification of Rail Thermal Stress Measurement System - Xiangyu, Duan; Liqiang, Zhu; Zujun, Yu; Xining, Xu (Periodica Polytechnica Transportation Engineering, 2020)
Continuous Welded Rail (CWR) is widely used in modern railways. With the absence of the expansion joints, CWR cannot expansion freely when the temperature changes, which could cause buckling in hot weather or breakage in cold weather. Therefore, rail thermal stress measuring system plays an important role in the safe operation of railways. This paper designed a thermal stress measurement system based on the acoustoelastic effect of the ultrasonic guided wave. A large-scale rail testbed was built to simulate the thermal stress in the rail track, and to establish the relationship of time-delay of guided wave and thermal stress. After laboratory testing, the system was installed in several railway lines in China for field tests. The results showed that the system was stable and accurate in stress measurement. The performance and potentials of the system were discussed.